Influence of Lime and Coal Bottom Ash as Partial Cement Replacement Material on Mechanical Properties of Concrete - Wan Ibrahim, Mohd Haziman; Mangi, Sajjad Ali; Mohammed Al-Fasih, Mohammed Yahya (International Journal of Sustainable Construction Engineering and Technology, 2021)
Coal bottom ash (CBA) is waste material like coarse sand collected at the bottom of the furnace during the power generation at the coal operated power plants. However, its huge production becomes a major issue that will bring a negative impact on the environment as it will lead to a higher risk of groundwater contamination. In this study, 10% of CBA with proportions of 5%, 10%, and 15% of lime were used to replace the cement by weight, respectively. A slump test was conducted to measure the workability property. The compressive strength test, split tensile strength test and flexural strength test was carried out after 7 days and 28 days of the curing. Based on the results, the workability of concrete showed a reduction when the cement replacement level increased. The compressive, splitting tensile, and flexural strengths were reduced when cement replacement level increase but the strength was increased with the increase in curing age. However, the concrete containing 10% CBA showed higher split tensile strength than the control.